Occupant injury in rollover crashes – Contribution of planar impacts with objects and other vehicles. (December 2015) - Ivarsson, Johan; Poplin, Gerald; McMurry, Tim; Crandall, Jeff; Kerrigan, Jason
Highlights: We compare injury and other characteristics of pure and multi-event rollover crashes. Pure and single vehicle primary rollover crashes can be considered collectively. Planar impact contributes to injury in non-primary crashes with 0 or 1 roof inversion. Abstract: Planar impacts with objects and other vehicles may increase the risk and severity of injury in rollover crashes. The current study compares the frequency of injury measures (MAIS 2+, 3+, and 4+; fatal; AIS 2+ head and cervical spine; and AIS 3+ head and thorax) as well as vehicle type distribution (passenger car, SUV, van, and light truck), crash kinematics, and occupant demographics between single vehicle single event rollovers (SV Pure) and multiple event rollovers to determine which types of multiple event rollovers can be pooled with SV Pure to study rollover induced occupant injury. Four different types of multiple event rollovers were defined: single and multi-vehicle crashes for which the rollover is the most severe event (SV Prim and MV Prim) and single and multi-vehicle crashes for which the rollover is not the most severe event (SV Non-Prim and MV Non-Prim). Information from real world crashes was obtained from the National Automotive Sampling System – Crashworthiness Data System (NASS-CDS) for the period from 1995 through 2011. Belted, contained or partially ejected, adult occupants in vehicles that completed 1–16 lateral quarter turns were assigned to one of the five rollover categories. The results showed that the frequency of injury in non-primary rollovers (SV Non-Prim and MV Non-Prim) involving no more than one roof inversion is substantially greater than in SV Pure, but that this disparity diminishes for crashes involving multiple inversions. It can further be concluded that for a given number of roof inversions, the distribution of injuries and crash characteristics in SV Pure and SV Prim crashes are sufficiently similar for these categories to be considered collectively for purposes of understanding etiologies and developing strategies for prevention.